Mesoporous Silica Nanoparticle-Coated Microneedle Arrays for Intradermal Antigen Delivery - Tu, Jing (Pharm Res, 2017)
PURPOSE: To develop a new intradermal antigen delivery system by coating microneedle arrays with lipid bilayer-coated, antigen-loaded mesoporous silica nanoparticles (LB-MSN-OVA). METHODS: Synthesis of MSNs with 10-nm pores was performed and the nanoparticles were loaded with the model antigen ovalbumin (OVA), and coated with a lipid bilayer (LB-MSN-OVA). The uptake of LB-MSN-OVA by bone marrow-derived dendritic cells (BDMCs) was studied by flow cytometry. The designed LB-MSN-OVA were coated onto pH-sensitive pyridine-modified microneedle arrays and the delivery of LB-MSN-OVA into ex vivo human skin was studied. RESULTS: The synthesized MSNs demonstrated efficient loading of OVA with a maximum loading capacity of about 34% and the lipid bilayer enhanced the colloidal stability of the MSNs. Uptake of OVA loaded in LB-MSN-OVA by BMDCs was higher than that of free OVA, suggesting effective targeting of LB-MSN-OVA to antigen-presenting cells. Microneedles were readily coated with LB-MSN-OVA at pH 5.8, yielding 1.5 μg of encapsulated OVA per microneedle array. Finally, as a result of the pyridine modification, LB-MSN-OVA were effectively released from the microneedles upon piercing the skin. CONCLUSION: Microneedle arrays coated with LB-MSN-OVA were successfully developed and shown to be suitable for intradermal delivery of the encapsulated protein antigen. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11095-017-2177-4) contains supplementary material, which is available to authorized users.